Cerebellum abnormalities in vascular mild cognitive impairment with depression symptom patients: A multimodal magnetic resonance imaging study - Yirong Chen; Liling Chen; Liyu Hu; Jianjun Wang; Jinhuan Zhang; Hanqing Lyu; Jinping Xu; Jianxiang Chen; Haibo Yu (Brain Research Bulletin)
Background: Subcortical vascular mild cognitive impairment (svMCI) frequently occurs alongside depression symptoms, significantly affecting patients' quality of life. While cognitive decline and depression symptoms are linked to cerebellar changes, the specific relationship between these changes and cognitive status in svMCI patients with depression symptoms remains unclear. Objective: This study aimed to investigates the gray matter volume and functional alterations in the cerebellum of svMCI patients, with and without depression symptoms, and their correlation with cognitive and depressive symptoms. Methods: We enrolled 16 svMCI patients with depression symptoms (svMCI+D), 15 without (svMCI-D), and 12 normal controls (NC). Multimodal MRI scans were conducted, assessing gray matter volume and resting-state functional connectivity (RSFC) in the cerebellum. Correlations between RSFC and clinical scores from the Montreal Cognitive Assessment (MoCA) and Hamilton Depression Scale (HAMD) were analyzed. Results: Structural analysis indicated gray matter atrophy in left cerebellar lobules I_IV and VI (Cere6.L) in svMCI patients. svMCI+D patients showed reduced RSFC between Cere6.L and left cerebellar region IX and the left superior frontal gyrus (SFGdor.L). Both svMCI+D and svMCI-D groups showed increased RSFC between Cere6.L and the right caudate nucleus. RSFC between Cere6.L and SFGdor.L correlated negatively with HAMD scores in svMCI+D and positively with MoCA scores in svMCI-D. RSFC between Cere6.L and the right caudate nucleus also correlated positively with MoCA in the svMCI-D. Conclusion: Cerebellar abnormalities, including the gray matter atrophy and RSFC changes, are associated with svMCI, particularly when depression symptoms are present. These results suggest potential diagnostic and therapeutic implications for svMCI and emphasize the need for further research on the cerebellum's role in cognitive and emotional disorders.